2015
DOI: 10.1002/ece3.1725
|View full text |Cite
|
Sign up to set email alerts
|

Release from belowground enemies and shifts in root traits as interrelated drivers of alien plant invasion success: a hypothesis

Abstract: Our understanding of the interrelated mechanisms driving plant invasions, such as the interplay between enemy release and resource‐acquisition traits, is biased by an aboveground perspective. To address this bias, I hypothesize that plant release from belowground enemies (especially fungal pathogens) will give invasive plant species a fitness advantage in the alien range, via shifts in root traits (e.g., increased specific root length and branching intensity) that increase resource uptake and competitive abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 132 publications
(167 reference statements)
0
15
0
Order By: Relevance
“…There is increasing evidence that belowground enemies can be as important for species co-existence and community dynamics as aboveground enemies [62] and may even drive the positive biodiversity-productivity relationships in native plant communities [63]. Nevertheless, surprisingly few studies have looked on enemy release from belowground enemies [52,64] and most of them concentrated on plant-soil feedback (e.g., [65][66][67][68][69][70][71][72]. These studies frequently demonstrated that release from soil-borne pathogens may favor plant invasions [52,64], but the role of belowground insect herbivory is still insufficiently understood and studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing evidence that belowground enemies can be as important for species co-existence and community dynamics as aboveground enemies [62] and may even drive the positive biodiversity-productivity relationships in native plant communities [63]. Nevertheless, surprisingly few studies have looked on enemy release from belowground enemies [52,64] and most of them concentrated on plant-soil feedback (e.g., [65][66][67][68][69][70][71][72]. These studies frequently demonstrated that release from soil-borne pathogens may favor plant invasions [52,64], but the role of belowground insect herbivory is still insufficiently understood and studied.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, surprisingly few studies have looked on enemy release from belowground enemies [52,64] and most of them concentrated on plant-soil feedback (e.g., [65][66][67][68][69][70][71][72]. These studies frequently demonstrated that release from soil-borne pathogens may favor plant invasions [52,64], but the role of belowground insect herbivory is still insufficiently understood and studied. Root herbivores are increasingly used as biocontrol agents [73] as they are highly specific and can effectively reduce growth and survival of focal plants species (e.g., [74].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These belowground differences between Leymus and Ammophila were unaltered by interactions with AMF or PPN. Inherent differences in root architecture, and the associated differences in response to root herbivores, including PPN, may provide a possible explanation for the invasion success of many exotic invasive plant species (Dawson 2015).…”
Section: Discussionmentioning
confidence: 99%